PROSPECTS OF APPLICATION OF GAS-OIL BLOCKS WITH THE PURPOSE OF REDUCING HEAVY METAL EMISSIONS - Меренгер, Петр; Шелеш, Татьяна; Малеваный, Евгений; Пятачук, Вячеслав; Беднарская, Инна (SWorldJournal, 2020)
During the combustion of fuel oil at the power plant, heavy metal compounds are formed. Vanadium compounds are the main components of fuel oil ash, so the amount of vanadium emissions is taken as a control parameter of the harmful effects of fuel oil on